Perubahan Perilaku Wajib Pajak Dalam Perencanaan Pajak Pasca Implementasi Sistem Coretax - Ita Salsalina Lingga; Budi Ismanto Prasetyo; Dadang Wahyudi Wahyu; Muhammad Lutfi Ulfa (Journal of Accounting, Finance, Taxation, and Auditing (JAFTA), 2026)
Tax planning is regarded as a form of tax avoidance, but if tax avoidance is carried out aggressively, it can be categorized as tax evasion. The implementation of the Coretax system is considered capable of preventing tax evasion behavior that has been widely practiced, thereby increasing tax compliance. There has not been much research conducted regarding the impact of Coretax implementation on tax avoidance behavior. This has prompted the conducting of this research with the aim of proving whether changes in tax planning behavior are influenced by perception of transparency and perception of tax audit risk. PLS-SEM was chosen as the method used in data processing with results showing that changes in tax planning behavior are influenced by perception of transparency and perception of tax audit risk. It is proven that the perception of tax audit risk has a greater influence compared to the perception of transparency. Concerning about the risk of future audits have a greater impact on taxpayers’ behavior in tax planning therefore prefer choosing not to engage in aggressive tax planning.